The study of Psychiatric Disorders in patients with Thyroid Disorder at the tertiary care centre in Western Region of Nepal (Journal of Psychiatrists' Association of Nepal, 2014)
Background:Recent advances in biotechnology have led to an improved understanding of the impact of thyroid functions on the adult, mature brain. This development has been particularly helpful in elucidating the role of thyroid hormones in the pathophysiology of psychiatric disorders. The aim of the study was to evaluate the occurrence of various psychiatric disorders in adult patients affected by different thyroid disorders.   Methods and materials:This was a descriptive, cross- sectional, hospital based and a collaborative study between the internal medicine and the psychiatry department at Gandaki Medical College, Pokhara, Nepal. Based on the ICD- 10 psychiatric diagnosis, 60 consecutive consenting subjects of any gender above 18 years of age were included in the study. The duration of the study was 6 months.   Results:The total numbers of subjects enrolled in the study were 60. The female consisted of 81.7% (49). The mean age was 39.62 ± 12.85 years. Regarding the thyroid disorder; 76.7% (46) had hypothyroidism, 15% (9) had sub clinical hypothyroidism, and both the hyperthyroidism and Hashimoto thyroiditis were found in 3.3% (2) of the cases while papillary carcinoma was found in 1.7% (1) case. Determination of psychiatric co-morbidity showed that; greater numbers of the subjects i.e. 48.3% (29) had neurotic, stress- related and somatoform disorders (F40- F48), 26.7% (16) had mood (affective) disorder (F30- F39), 13.3% (8) had simultaneously two psychiatric disorder, 10% (6) had headache and only 1.7% (1) had lack or loss of sexual desire (F52.0).   Conclusion: Compared to males, Females are more likely to have thyroid disorder. Clinician has to be alert to the possible underlying psychiatric disorder in subjects with any thyroid disorder. DOI: http://dx.doi.org/10.3126/jpan.v2i2.9723 J Psychiatrists’ Association of Nepal Vol.2, No.2, 2013 29-34